Molecular docking study of natural compounds from red betel (Piper crocatum Ruiz & Pav) as inhibitor of secreted aspartic proteinase 5 (Sap 5) in Candida albicans - Gusnia Meilin Gholam; Iman Akhyar Firdausy (Universitas Mataram, 2022)
Candida albicans can cause adverse infections in humans. The targeting of Sap 5 is due to its virulence factor in C. albicans. The method used is molecular docking using YASARA structure and BIOVIA Discovery Studio. The purpose of this study was to investigate the molecular interaction between red betel and Sap 5 as a potential inhibitor of C. albicans in infecting humans. The results showed that CHEMBL216163 (9,644 kcal/mol) and MLS000557666 (9,525 kcal/mol) have Binding energy above Pepstatin (9,484 kcal/mol) and affect the active site of Sap 5 so that the two test ligands could be further analyzed.